Immobilization Technologies in Probiotic Food Production - Gregoria Mitropoulou; Viktor Nedovic; Arun Goyal; Yiannis Kourkoutas (Journal of Nutrition and Metabolism)
Various supports and immobilization/encapsulation techniques have been proposed and tested for application in functional food production. In the present review, the use of probiotic microorganisms for the production of novel foods is discussed, while the benefits and criteria of using probiotic cultures are analyzed. Subsequently, immobilization/encapsulation applications in the food industry aiming at the prolongation of cell viability are described together with an evaluation of their potential future impact, which is also highlighted and assessed.